Claim For Compensation For Land In Court Ruling Number 53/Pdt.G/2019/Pn.Cjr Based On Principal Agrarian Law - Riza Zulfikar; Hadi Purnomo (Jurnal Sosial Sains dan Komunikasi, 2023)
With the implementation of Mediation in Court through the results of Court Decision Number 53/Pdt.G/2019PN.Cjr, a provision applies which requires that all civil cases registered in the District Court must first attempt to resolve the dispute through a mediation process, including cases of claims for compensation in land dispute in Court Decision Number 53/Pdt.G/2019PN.Cjr. Based on the Basic Agrarian Law. Based on this, the issues that will be discussed are first, how the judge considers the plaintiffs' claim for compensation for the issuance of the certificate of rights in Court Decision Number 53/Pdt.G/2019/PN.Cjr, second, what legal remedies can be taken by the parties. In this writing, the author uses empirical juridical research methods, using primary data and secondary data, while data collection techniques are in the form of library studies and field studies, namely interviews and document studies. From the research results, it can be concluded that Court Decision Number 53/Pdt.G/2019/PN.Cjr, the researcher considers that the judge's decision stating that the claim for compensation for the Plaintiffs' rights is declared unacceptable due to formal defects is correct and the researcher assesses that that the judge's decision stating that the development of the disputed land belongs to Cipanas Village so that it is within the authority of the property rights to be able to use it and to take other legal action is correct.